In-band OSNR monitoring using a pair of Michelson fiber interferometers - Donegan, John; Bradley, Louise (My University, 2010)
Two polarization-independent Michelson fiber inter ferometers with different optical delays were used to measure the in-band OSNR of an optical signal from 5 to 30dB within an accuracy of 0.5dB. Using an expansion of the amplitude autocorrelation function of the signal around zero delay, it was possible to perform measurements without any prior knowledge of the signal. The system is shown to be immune to the effects of modulation frequency (up to 10G), partially and fully polarized noise, chromatic dispersion and poorly biased modulators.
PUBLISHED
Keywords: Michelson fiber; Michelson fiber